2019
DOI: 10.1016/j.rmcr.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary mucormycosis associated with medical marijuana use

Abstract: A 66-year-old man with diabetes presented to the hospital with a two-month history of dyspnea, cough, rust-colored sputum, night sweats and 20 pound weight loss. He had begun smoking medical marijuana 3 months earlier. CT of the chest showed multiple bilateral large ground glass opacities with surrounding consolidation. Infectious workup was negative. BAL was non-diagnostic. He was treated with broad spectrum antibiotics without improvement. VATS was performed and cultured lung tissue grew Rhizopus species. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Case reports [66][67][68][69][70] describing the effect of smoking, vaping, or inhaling aerosolized contaminated marijuana demonstrate some of the graver risks to patients, especially those with leukemia, lymphoma, AIDS, or those with medical conditions requiring immune-suppressing therapies. However, the disease has also been noted in non-immunocompromised patients, albeit at a less frequent rate.…”
Section: Risks and Effects Of Consumption Of Contaminated Cannabismentioning
confidence: 99%
“…Case reports [66][67][68][69][70] describing the effect of smoking, vaping, or inhaling aerosolized contaminated marijuana demonstrate some of the graver risks to patients, especially those with leukemia, lymphoma, AIDS, or those with medical conditions requiring immune-suppressing therapies. However, the disease has also been noted in non-immunocompromised patients, albeit at a less frequent rate.…”
Section: Risks and Effects Of Consumption Of Contaminated Cannabismentioning
confidence: 99%
“…following marijuana use. 16 For instance, a recent case study documented the case of a diabetic patient who passed away after getting diagnosed with pulmonary mucormycosis. 16 Further investigation revealed that he had begun smoking medical marijuana only 3 months before his diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“… 16 For instance, a recent case study documented the case of a diabetic patient who passed away after getting diagnosed with pulmonary mucormycosis. 16 Further investigation revealed that he had begun smoking medical marijuana only 3 months before his diagnosis. It was hypothesized that the combination of poorly controlled diabetes and emphysema caused by extensive cigarette smoking made him more susceptible to acquire this fungal infection.…”
Section: Resultsmentioning
confidence: 99%
“…CotH is a fungal spore coat protein present in Mucorales species and functions as a ligand that can bind to GRP78, facilitating angioinvasion. 3 , 4 Moreover, hyperglycemia and ketoacidosis act to suppress the innate immune system in addition to facilitating an optimal environment for fungal proliferation. 3 , 4 Gender – Incorrect.…”
mentioning
confidence: 99%
“…3 , 4 Moreover, hyperglycemia and ketoacidosis act to suppress the innate immune system in addition to facilitating an optimal environment for fungal proliferation. 3 , 4 Gender – Incorrect. Gender is not an independent risk factor for the development of mucormycosis.…”
mentioning
confidence: 99%